ANALISIS PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. INTI TELEKOMUNIKASI - M. TAHER RAMBE (LP2MTBM MAKARIOZ, 2021)
To build a strong organizational culture requires a process because the changes that occur in the organization concern thechanges of employees who are in the organization or company including differences in perceptions, desires, attitudes, andbehaviors. Success or not effort in achieving the goals of the company or organization is also influenced by the high lowperformance of employees. Performance refers to the level of success in carrying out tasks and the ability to achievepredetermined goals. Performance is declared good and successful if the desired goal is achieved well. Organizationalculture is a characteristic of an organization, not an individual member. If an organization is equated with a human being,then organizational culture is a personality or personality of the organization. However, organizational culture shapes thebehavior of its member organizations, even not infrequently the behavior of members of the organization as individuals.Performance in general can be interpreted as the result of work in the quality and quantity achieved by an employee in theability to carry out tasks in accordance with the responsibilities given by superiors to him.